Factors affecting Firm Value of Miscellaneous Industry Companies on Indonesia Stock Exchange - Dieky Wilsen; Stella Stella (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to analyze the influence of leverage, dividend policy, effectiveness, efficiency and firm size to firm value with Ln stock price proxy, and compare it to prior research that correlates with this research. Data used in this research is the annual financial statements of miscellaneous industry companies, which is listed in Indonesia Stock Exchange 2012-2020 period. The sampling method used in this research is purposive sampling, which 5 companies met the criteria, and analyzed using panel data with fixed effect model. The result of this research indicates that leverage, dividend policy, efficiency and firm size don’t influence firm value, while efficiency has an influence on firm value.